ANALYSIS OF CONSUMER ONLINE SHOPPING BEHAVIOR IN THE MARKET PLACE CONTEXT IN INDONESIA - Ekowati, Titin; Widjajani, Susi; Puspitasari, Intan; Ariningsih, Endah Pri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Online purchasing behavior is the process of buying products via the internet and the process has different steps unlike physical purchasing behavior. This research aims to analyze consumer online shopping behavior by identifying consumer online purchasing behavior in the form of consumer experience in online shopping which is formed from online shopping orientation, online shopping experience, and online shopping trust in marketplaces in Indonesia. This research uses a phenomenological design to explore and analyze data. The research findings show that almost all participants carry out online shopping activities related to three aspects that form online shopping behavior, namely online shopping orientation, online shopping experience, and online shopping trust. The participants experience in doing online shopping is because there is a comfort orientation, a pleasant experience, and they already understand that online stores can be trusted as a destination for online shopping activities.